THE INFLUENCE OF ORGANIZATIONAL SUPPORT AND RESILIENCE ON ORGANIZATIONAL COMMITMENT WITH JOB SATISFACTION AS A MEDIATING VARIABLE IN TEACHERS IN THE LABSCHOOL ENVIRONMENT - Sholikhah; Wolor, Christian Wiradendi; Malzara, Vidia Ratu Balqis (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2023)
The purpose of this study was to determine the organizational commitment of junior and senior high school teachers in the Labschool environment both located in Rawamangun and Kebayoran. The research method used in this research is descriptive and explanatory research. The population of this study were all 240 teachers of the Labschool environment with a sample taken as many as 186 people. The data that has been obtained will be processed and analyzed using Statistical Product and Service Solutions (SPSS) and LISREL software. The results found that Organizational Support and Resilience directly have a positive and significant effect on Job Satisfaction. In addition, Organizational Support, Resilience, and Job satisfaction directly have a positive and significant effect on Organizational Commitment. Finally, Organizational Support and Resilience indirectly have a positive and significant effect on Organizational Commitment through Job Satisfaction.